2020
DOI: 10.14414/jebav.v23i2.2326
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Audit Fees on the Effect of Task Complexity and Independence towards Audit Judgment

Abstract: This study examines the effect of task complexity and auditor independence on audit judgment with audit fees as a moderating variable. Samples were obtained from auditors working in public accounting firms in West Jakarta and South Jakarta. Data collection was done using a survey method by distributing questionnaires to 100 auditors as respondents. The method of analysis used was Moderated Regression Analysis. The results show that task complexity hurts audit judgment. Auditor independence has a positive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Task complexity is a form of complex task, consisting of many parts and interrelated with each other. Previous research conducted by (Raihanah et al, 2022), Eny & Mappanyukki, (2020), Aida et al, (2021) found that taskicomplexity had a negative(-) effect on audits. Based on the discussion, the hypotheses of this research are: H3: Taskicomplexityihasiainegativeieffectioniauditijudgment.…”
Section: Theieffect Ofitask Complexityioniauditijudgmentmentioning
confidence: 88%
“…Task complexity is a form of complex task, consisting of many parts and interrelated with each other. Previous research conducted by (Raihanah et al, 2022), Eny & Mappanyukki, (2020), Aida et al, (2021) found that taskicomplexity had a negative(-) effect on audits. Based on the discussion, the hypotheses of this research are: H3: Taskicomplexityihasiainegativeieffectioniauditijudgment.…”
Section: Theieffect Ofitask Complexityioniauditijudgmentmentioning
confidence: 88%
“…Audit fees also act as moderation. For example, a study by Eny and Mappanyukki (2020) concluded that audit fees moderate the influence of independence on audit judgment in Indonesia. Table 1 presents a summary of the factors influencing the size of external audit fees recapitulated from research evidence in various countries.…”
Section: External Audit Feementioning
confidence: 99%
“…Etika profesi merupakan salah satu komponen yang mempengaruhi kualitas audit dan dapat mengurangi risiko salah saji dalam penyajian laporan keuangan (Ika & Suryani, 2019). Profesionalisme dan pengalaman dapat mempengaruhi tingkat materialitas yang dipertimbangkan oleh auditor (Eny & Mappayukki, 2020). Spesialisasi profesional dapat meningkatkan kualitas audit dan mengurangi potensi efek negatif dari rotasi wajib KAP terhadap kualitas audit (Elshawarby, 2017).…”
Section: Pendahuluanunclassified